KELAYAKAN LIMBAH RAMBUT SEBAGAI HAIR EXTENSION: KELAYAKAN LIMBAH RAMBUT SEBAGAI HAIR EXTENSION - Winda, Novia Restu Windayani; wilujeng, Biyan Yesi Wilujeng; Octaverina Kecvara Pritasari; Dilla Salsabila (Universitas Negeri Surabaya, 2022)
The barbered hair in the salon is rarely reused by salon owners, only a few of them are used for economic value. Hair resistance includes resistance to heat, and has a rough texture so that it can bind more strongly. Hair extension is waste that comes from hair beauty salons in the form of haircuts that can be formed into hair extensions for certain purposes for a woman. The purpose of this study is to determine the validity and feasibility of hair extensions based on hair waste through sensory tests and favorability tests. The research method uses experiments, research objects of hair waste for the manufacture of hair extensions. data collection using observation and documentation, data analysis using descriptive percentages. The results of the hair extension research made from real hair waste were declared valid by the validator. Sensory test feasibility results from panelists with 3 beautician teachers, 2 salon owners had an average of 83.33% The feasibility results of the favorability test with 15 panelists had an average of 91.67%. The conclusion of the study is that the hair extension is declared valid by the